Comparative Study on Infant Mortality and Fertility Among Rural, Tribal and Urban Slum Population in Balasore District of Orissa. Final Report - Planning Commission (Planning Commission)
IMR is taken as a robust indicator of quality of health services and the development status of a community. The IMR for Orissa continues to be unacceptably high estimated at 76 per 1000 five births at present In fact it is the 2nd highest among all the states in India. The high IMR is attributed to insignificant reduction in neo-natal deaths that accounts for 68% of infant deaths in Orissa against 58% at all India level. Maternal factors apart from other risk factors - exogenous and endogenous - located at household, community and institutional level, operating during ante/intra/perinatal stages play a strong role for early morbidity and mortality of neonates mediated by “low birth weight that accounts for 38% of all births in Orissa. As a rule, 80% of neonatal deaths and 50% of infant deaths occur in LBW babies.
Final Report Submitted to Planning Commission ser Section Yojana Bhawan, New Delhi